A Calixarene‐Based Metal–Organic Framework for Highly Selective NO2 Detection. Issue 39 (29th August 2018) - Schulz, Marcel; Gehl, Adrian; Schlenkrich, Jakob; Schulze, Hendrik A.; Zimmermann, Stefan; Schaate, Andreas
Abstract: A calixarene‐based metal–organic framework (Zr‐cal, [Zr6 O4 (OH)4 (FA)6 ]2 (cal)3 ], FA=formate, cal=1, 3‐alt‐25, 26, 27, 28‐tetrakis[(carboxy)methoxy]calixarene) was synthesized and characterized by single‐crystal X‐ray diffraction. The three‐dimensional framework is a 4, 6‐connected network of gar topology and exhibits two equal but nonintersecting three‐dimensional pore systems. It has a specific BET surface area of 670 m 2  g −1, and the calixarene cavities are accessible through the pore systems. The exposed calixarenes can be used for the visual detection and encapsulation of NO2 through the formation of deeply colored charge–transfer complexes inside the MOF. The highly selective complexation was analyzed by UV/Vis and IR spectroscopy, and the stability of the material was confirmed by powder X‐ray diffraction and 1 H NMR spectroscopy. Finally, the MOF was used as a sensor material in a home‐made sensor cell and showed high sensitivity for NO2 . Abstract : A zirconium‐based MOF with calixarene linkers was synthesized and characterized. It exhibits a complex three‐dimensional pore system that exposes the calixarenes for the selective detection of NO2 . The impressive and reversible color change from white to blue makes the material a visual sensor for NO2 at room temperature.